Prevalence and risk factors of hypertension among college freshmen in China - Qingqing Jiang (Nature Portfolio, 2021)
Abstract Hypertension is the leading single contributor to all-cause death and disability worldwide. However, there is scarce evidence on the prevalence and risk factors of hypertension for Chinese youth. This study aimed to investigate the prevalence of hypertension among Chinese college freshmen and to identify the influencing factors. We conducted a cross-sectional study of all freshmen from 2015 to 2017 at a university in Wuhan, China by physical examination and standard-structured questionnaire. The Pearson chi-square test was used to compare categorical variables. Forward stepwise logistic regression method was used in the multivariate analysis to identify independent predictors of hypertension in youth. A total of 12,849 participants were included, and the prevalence of hypertension of Chinese college freshmen was 4.3% (7.9% in men and 1.6% in women). Men had a higher risk of hypertension than women (odds ratio [OR]: 5.358, 95% confidence interval [CI]: 4.345–6.607, P < 0.001). Obese people were more likely to develop hypertension than those with normal body mass index (OR: 10.465, 95% CI: 8.448–12.964, P < 0.001). People with elevated resting heart rate (RHR) had a higher prevalence of hypertension (OR: 4.987, 95% CI: 3.641–6.832, P < 0.001). Staying up late (OR: 2.957, 95% CI: 2.482–3.523, P < 0.001), physical inactivity (OR: 4.973, 95% CI: 4.141–5.972, P < 0.001), living in urban district (OR: 1.864, 95% CI: 1.493–2.329, P < 0.001) and family history of cardiovascular diseases (CVDs) (OR: 2.685, 95% CI: 2.108–3.421, P < 0.001) were related to higher prevalence of hypertension in youth. Male, obesity, elevated RHR, physical inactivity and family history of CVDs were identified as important risk factors of hypertension in youth. These risk factors should be given more attention when designing and implementing the interventional programs.